Peri-urban agrifood systems and a landscape project in the southern Mediterranean. The case of the urban agglomeration of Sousse (Tunisia) - Hamrita, Abdelkarim; Jiménez, Daniel Ferrer; Rejeb, Hichem (Frontiers in Sustainable Cities, 2022)
Peri-urban agrifood systems are frequently submitted to urban pressure and other territorial fac-tors that call for study and detailed analyses from multiple standpoints and from the perspective of many disciplines. In particular, the present research focuses upon the case of the Sousse met-ropolitan region (Tunisia), where the concurrence of different factors (political, environmental, economic, etc.), together with clearly deficient regulations and uncontrolled urban development, is threatening the survival of a traditional agricultural model. The latter is vital with regard to ensuring the economic upkeep of a vast number of families and to making an active contribution to food security, with the resulting production of varied, fresh, top-quality proximity food. Herein we present a specific method which, based on the integrating and strategic significance of land-scapes, and on the Landscape Character Assessment methodology, employs the so-called “land-scape project” to strengthen the resilience and sustainability of Sousses’s peri-urban agriculture, thus avoiding the loss of a landscape heritage that has always been considered as crucial to the identity of the local people. The paper highlights the importance of putting forward a proposal for a green infrastructure, duly integrated within land planning instruments and in the construction and consolidation of a local and sustainable agri-food system. Furthermore, we emphasise the need to promote the figure of Agricultural Parks as instruments for management, promotion and development. We also draw attention to the need to modify the current forms of governance, and this calls for the leadership and involvement of the principal stakeholders of peri-urban agricul-ture: the farmers.